Benign Infantile Seizures (Fukuyama Syndrome) - J Gordon Millichap (Pediatric Neurology Briefs)
Benign infantile seizures (BIS), first described by Fukuyama (1963) as generalized convulsions were later reported as focal or partial seizures, mainly non-familial, and more recently as familial with autosomal dominance.